Empowering Preparation for Old Age: An Application of the SDU Health Care Project - Kwanyuen, Renu; Niputhuttapong, Somjit (Journal of Food Health and Bioenvironmental Science, 2023)
This article aims to explore the concepts of empowerment in personal preparation for middle and late adults as well as to describe the application of empowerment within the SDU health project as an empowerment mechanism. Empowerment might play as mediator to enhance an optimal preparation for old age in a completely age society among staffs at Suan Dusit University. The results showed that the empowerment to prepare for old age consists of five aspects: physical, emotional, economic, social and housing and includes the processes of selfassessment, problem identification, problem analysis, planning and implementation, which help to improve individuals’ awareness and preparation for old age, leading to active aging in an era of rapid change in which technology has become a part of people’s daily lives.